All-optical generation of millmeterwave carrier based on stimulated brillouin scattering - Shee, Yu Gang (2011)
The ever growing demand for delivering high speed data and networking the world fuels the interest of research on broadband access networks. As data rates increase, larger frequency bandwidths are required to support the transmission. illimeterwave frequency has been identified as the high speed data carrier in hybrid fiber opticmillimeterwave link, or known as Radio Over Fiber (ROF) systems. All-optical generation of millimeterwave carriers attracted much attention due to many advantages compared to electronic solutions. Optical heterodyning or known as optical mixing is one of the enabling technologies. Optical mixing of dual-wavelength laser source produces a beating frequency which is identical to the frequency offset between the two laser signals. Nonlinear Stimulated Brillouin Scattering (SBS) is attractive in the generation of RF carriers due to its existence in the optical fiber with low threshold power. The generation of RF carriers without the utilization of high frequency signal generator is demonstrated in this work based on nonlinear SBS. A novel configuration, namely double-Brillouinfrequency shifter (DBFS), is proposed for the generation of higher order Brillouin Stokes signals. The second order Brillouin Stokes signal (BS2) is generated from the Brillouin pump (BP) by circulating and isolating the first order Stokes signal in the fiber through a four-port circulator. Microwave carrier at frequency equivalent to twice the Brillouin frequency shift (2vB) is generated by heterodyning the BP with BS2. An average carrier frequency of 21.3968 GHz with phase noise as low as -58.67 dBc/Hz is measured. Generation of millimeterwave at 64 GHz is experimentally proven by channel filtering from a multiwavelength Brillouin-erbium fiber laser (BEFL). By incorporating the DBFS, a four-channel BEFL with channel spacing of 2vB is generated. A dualwavelength signal with ~64 GHz (6vB) spacing is obtained by suppressing the two channels at the middle from the BEFL output. Millimeterwave carrier at ~64 GHz is produced after heterodyne the dual-wavelength signal at a high speed photo detector. Multiband carrier generation is also achieved by a proper design of channel demultiplexer at the output of BEFL. Microwave carriers at ~19 GHz and millimeterwave carriers at ~59 GHz are simultaneously generated from a single BEFL. System performance is investigated based on the measurement of phase noise, frequency drift and power fluctuations of the generated signals. Temperature sensitive characteristic of Brillouin frequency shift is utilized in the frequency tuning of generated RF carrier. Investigation results show a linear relationship between the output frequency and the temperature increment. This realizes the frequency tunability of the generated carriers. With the novel configuration of DBFS, generation of microwave and millimeterwave carriers were realized through the heterodyning of Stokes signals. The cascaded Brillouin effect in DBFS enables double-Brillouin-frequency shifting at low threshold power. However, stability of stimulated Brillouin scattering in optical fiber needs to be improved with enhanced control mechanism in the future.